Lung-Specific Extracellular Superoxide Dismutase Improves Cognition of Adult Mice Exposed to Neonatal Hyperoxia - Buczynski, Bradley W.; Mai, Nguyen; Yee, Min; Allen, Joshua L.; Prifti, Landa; Cory-Slechta, Deborah A.; Halterman, Marc W.; O'Reilly, Michael A. (Frontiers in Medicine, 2018)
Lung and brain development is often altered in infants born preterm and exposed to excess oxygen, and this can lead to impaired lung function and neurocognitive abilities later in life. Oxygen-derived reactive oxygen species and the ensuing inflammatory response are believed to be an underlying cause of disease because over-expression of some anti-oxidant enzymes is protective in animal models. For example, neurodevelopment is preserved in mice that ubiquitously express human extracellular superoxide dismutase (EC-SOD) under control of an actin promoter. Similarly, oxygen-dependent changes in lung development are attenuated in transgenic SftpcEC-SOD mice that over-express EC-SOD in pulmonary alveolar epithelial type II cells. But whether anti-oxidants targeted to the lung provide protection to other organs, such as the brain is not known. Here, we use transgenic SftpcEC-SOD mice to investigate whether lung-specific expression of EC-SOD also preserves neurodevelopment following exposure to neonatal hyperoxia. Wild type and SftpcEC-SOD transgenic mice were exposed to room air or 100% oxygen between postnatal days 0-4. At 8 weeks of age, we investigated neurocognitive function as defined by novel object recognition, pathologic changes in hippocampal neurons, and microglial cell activation. Neonatal hyperoxia impaired novel object recognition memory in adult female but not male mice. Behavioral deficits were associated with microglial activation, CA1 neuron nuclear contraction, and fiber sprouting within the hilus of the dentate gyrus (DG). Over-expression of EC-SOD in the lung preserved novel object recognition and reduced the observed changes in neuronal nuclear size and myelin basic protein fiber density. It had no effect on the extent of microglial activation in the hippocampus. These findings demonstrate pulmonary expression of EC-SOD preserves short-term memory in adult female mice exposed to neonatal hyperoxia, thus suggesting anti-oxidants designed to alleviate oxygen-induced lung disease such as in preterm infants may also be neuroprotective.